STRATEGI PEMBELAJARAN KOOPERATIF ( COOPERATIVE LEARNING ) GURU PENDIDIKAN AGAMA ISLAM ( PAI ) DALAM MENINGKATKAN KEMAMPUAN HASIL BELAJAR SISWA - Siti Ruhilatul Jannah; Nur Aisyah (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
The low quality of learning is one of the problems currently faced in the world of education, such as the learning process of Islamic religious education (PAI). This study aims to determine how Islamic religious education (PAI) teachers in the classroom use cooperative learning strategies to improve student learning outcomes. The cooperative learning strategy is one way of striving for student learning experiences to be more active, this affects the development or abilities of students both in terms of cognitive and psychomotor in it. This study uses a qualitative approach with observation and interview procedures to describe the overall learning process as well as the evaluation process. The results of this study indicate learning using cooperative strategies has increased the learning outcomes of students. Judging from the development of student understanding in the classroom.